CXCL12 in astrocytes contributes to bone cancer pain through CXCR4-mediated neuronal sensitization and glial activation in rat spinal cord - Shen, Wen (BioMed Central, 2014)
BACKGROUND: Previous studies have demonstrated that chemokine CXCL12 and its receptor CXCR4 are critical for pain sensitization, but the mechanisms involved are not clear. In this study, we investigated the specific cellular mechanisms of CXCL12/CXCR4 chemokine signaling in the development and maintenance of bone cancer pain after tumor cell implantation (TCI). METHODS: TCI in the tibial cavity of rats was used to establish a bone cancer pain model. Mechanical allodynia and thermal hyperalgesia were determined by measuring the paw withdrawal threshold and latency, respectively. The protein expression and cellular localization of CXCL12 and CXCR4 were detected by western blot and immunofluorescence staining. The sensitization of neurons, activation of astrocytes and microglia were examined by observing the immunofluorescence intensity of c-Fos, GFAP and IBA1. RESULTS: Our results demonstrated that CXCL12 was upregulated in a time-related manner, both in the dorsal root ganglia and spinal cord after TCI. Spinal CXCL12 was predominately expressed in astrocytes, and an intrathecal injection of astrocyte metabolic inhibitor fluorocitrate or selective JNK inhibitor SP600125 abolished TCI-induced CXCL12 production. A single intrathecal injection of a CXCL12 neutralizing antibody (10 μg/10 μl) at day 10 after TCI transiently reversed bone cancer pain in a dose-dependent manner. Whereas repetitive intrathecal administration of a CXCL12 neutralizing antibody (10 μg/10 μl, once a day from day 3 to 5 after TCI) significantly delayed the onset of TCI-induced pain behaviors for nearly five days. Spinal CXCR4 was also upregulated after TCI and colocalized with neurons, astrocytes and microglia. Blocking CXCR4 suppressed TCI-induced activation of neurons, astrocytes and microglia in the spinal cord at day 14. Repeated intrathecal administration of AMD3100 (5 μg/10 μl, once a day for three days) significantly delayed and suppressed the initiation and persistence of bone cancer pain in the early phase (at day 5, 6 and 7 after TCI) and in the late phase (at day 12, 13 and 14 after TCI) of bone cancer, respectively. CONCLUSIONS: Taken together, these results demonstrate that CXCL12/CXCR4 signaling contributed to the development and maintenance of bone cancer pain via sensitizing neurons and activating astrocytes and microglia. Additionally, this chemokine signaling may be a potential target for treating bone cancer pain.